2004
DOI: 10.1149/1.1646148
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Water Transport in Gas Diffusion Layer of Polymer Electrolyte Fuel Cells

Abstract: High-current-density performance of polymer electrolyte fuel cells ͑PEFCs͒ is known to be limited by transport of reactants and products. In addition, at high current densities, excessive amount of water is generated and condenses, filling the pores of electrodes with liquid water, and hence limiting the reactant transport to active catalyst. This phenomenon known as ''flooding'' is an important limiting factor of PEFC performance. In this work, the governing physics of water transport in both hydrophilic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
430
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 640 publications
(449 citation statements)
references
References 17 publications
15
430
0
4
Order By: Relevance
“…9 It must also permit transport of gas reactants and liquid product between the gas flow channels and the catalyst/PEM interface. 4,10,11 The porous electrode, or gas diffusion layer (GDL), of the fuel cell is typically made from carbon fibers, either as a random sheet of fibers in the form of carbon paper or as a woven array of fiber bundles forming carbon cloth. 12,13 These sheets of carbon fibers may be treated with adsorbed polymer layers to improve their function in fuel cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 It must also permit transport of gas reactants and liquid product between the gas flow channels and the catalyst/PEM interface. 4,10,11 The porous electrode, or gas diffusion layer (GDL), of the fuel cell is typically made from carbon fibers, either as a random sheet of fibers in the form of carbon paper or as a woven array of fiber bundles forming carbon cloth. 12,13 These sheets of carbon fibers may be treated with adsorbed polymer layers to improve their function in fuel cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several studies have been conducted on two-phase flows in PEM fuel cells. Theoretical one-dimensional models for liquid water transport in gas diffusion layers (GDLs), where liquid water is controlled by capillary forces depending on the structure and wettability of GDL, have been reported [1,2], and three-dimensional simulations using two-phase models have been developed [3,4]. For liquid water transport in gas flow channels, experimental investigations have been conducted using transparent fuel cells and it was demonstrated that the surface tension of water and the wettability of the GDL and gas flow channel play a dominant role in the liquid water transport [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, deficiency of water decreases the proton conductivity of the membrane and thus humidification of reactants is typically needed. Water management has a considerable effect on fuel cell performance and the process is highly sensitive to operational and material parameters [9][10][11][12][13]. Water transport inside the fuel cell has a close link to temperature distribution since water and oxygen diffusivity, saturation parameters, and reaction kinetics are all temperature dependent, see, e.g.…”
Section: Introductionmentioning
confidence: 99%